Interpersonal Communication Analysis In Improving Work Ethic - Silviani, Irene; Yudhi, Lim (Jurnal Mamangan, 2023)
Communication is the process of exchanging information, ideas, feelings and attitudes between two or more people using verbal or nonverbal symbols. This research aims to analyze the interpersonal communication skills of leaders in improving work ethics at the East Medan Subdistrict Office, Medan City. This research uses a descriptive method with qualitative analysis techniques. In this study, the research subjects were: (a) Key informant, Head of East Medan District, Medan City; (b) Main informant, Secretary of East Medan Subdistrict Head, Medan City; (c) Additional informants, East Medan District Community Figures, and Youth Leaders in East Medan District and Head of General Subdivision of the East Medan District Head Office, Medan City. Data collection in research uses primary data and secondary data. Primary data is data obtained from direct observation in the field by studying and observing the physical condition of the area as well as conducting interviews with various sources such as the Head of the East Medan Subdistrict, Medan City, the Secretary of the Head of the District and Community Leaders, Youth Leaders and the Head of General Subdivision of the East Medan Subdistrict Office, Medan City. Primary Data Collection can be obtained through several methods, namely as follows: (a) Observation; (b) Documentation; and (c) Interview. Meanwhile, data analysis techniques use: (a) Data Reduction; (b) Data Presentation; and (c) Verification. Based on the research results, the following results were obtained in the form of: (1) Interpersonal communication in the East Medan Subdistrict office, Medan City, has been going very well; (2) Based on the results of the researcher's observations for 2 (two) months at the East Medan Subdistrict Office, Medan City, several things can be found related to the dimensions of interpersonal communication between leaders and employees in improving work ethics as follows: (a) Openness, Leaders of the East Medan Subdistrict Office The city of Medan really upholds the principle of openness, especially regarding criticism and suggestions submitted to the leadership. (b) Empathy, the Head of the East Medan Subdistrict Office, Medan City, always shows empathy in the interpersonal communication model used. (c) Supportive Attitude, the Head of the East Medan Subdistrict Office, Medan City, always expresses his support through praise spoken directly to his employees. (d) Positive attitude, the editor-in-chief shows a positive feeling when communicating by providing ethics and professionalism. (e) Similarity, the Head of the East Medan Subdistrict Office, Medan City, considers the way of communicating with superiors, senior employees and junior employees to be the same. (3) Based on the results of the researcher's observations for 2 (two) months at the East Medan Subdistrict Office, Medan City, several things can be found related to the interpersonal communication model between leaders and employees in providing work motivation at the East Medan Subdistrict Office, Medan City using an interactive model. In this case, the leadership of the East Medan Subdistrict Office, Medan City, always provides opportunities for employees within it to respond to information or messages conveyed by the leadership.